2019
DOI: 10.11114/jets.v7i10.4425
|View full text |Cite
|
Sign up to set email alerts
|

The Change in ELT Pre-service Teachers’ Cognition During Teaching Practicum

Abstract: The aim of this study was to examine the change of ELT pre-service teachers" cognition during teaching practicum uncovering their beliefs regarding language teaching, being a teacher and dynamics of practicum. To adopt a comprehensive perspective on how the participants" cognition evolved as a result of practicum, qualitative research design with open-ended surveys before and after the practicum process was conducted with ELT pre-service teachers. The findings were evaluated and discussed in terms of a certain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Slightly different from Hollingsworth (1989) , whose cognition changes for pre-service teachers are only positive. The findings of this study are similar to the results of Yüksel and Başaran (2019) research, which proves that as the learning process progresses, student cognition changes are diverse and dynamic due to various factors that occur from pre-service teachers themselves and also the factors around them during the educational process they undergo.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Slightly different from Hollingsworth (1989) , whose cognition changes for pre-service teachers are only positive. The findings of this study are similar to the results of Yüksel and Başaran (2019) research, which proves that as the learning process progresses, student cognition changes are diverse and dynamic due to various factors that occur from pre-service teachers themselves and also the factors around them during the educational process they undergo.…”
Section: Discussionsupporting
confidence: 86%
“…Another study on changes in cognition of pre-service teachers was also conducted by Yüksel and Başaran (2019) , where they investigated changes in cognition of pre-service ELT teachers during teaching practicum. Yüksel and Başaran (2019) revealed the beliefs of pre-service teachers about language teaching, the dynamics of teaching practicum in the classroom, and the belief in being a teacher. The results of their research implied the complexity of the practicum process in pre-service teacher cognition.…”
Section: Literature Reviewmentioning
confidence: 99%
“…After two years of full-time teaching, participants felt that the teacher education program equipped them with useful theoretical tools, but they realized that school expectations limited their autonomy. In contrast, Yüksel and Başaran (2019) found that practicum provided preservice teachers with a real-life experience allowing them to transfer some of their beliefs as learners into their teaching practice.…”
Section: The Effects Of Practicum On Esl/efl Preservice Teacher Cogni...mentioning
confidence: 88%
“…When pre-service teachers bring their own beliefs into teacher education programs, their beliefs usually guide their actions. In the literature, different aspects of pre-service teacher beliefs have been studied in the Turkish context, such as efficacy beliefs (Eren & Yeşilbursa, 2019), emotional intelligence and beliefs (Öz & Çepik Kiriş, 2018), career development and leadership aspirations (Ölçü-Dinçer & Seferoğlu, 2018), change in cognition after practicum (Debreli, 2016;Kavanoz et al, 2017;Yüksel & Başaran, 2019), and changes in concerns about teaching (Yalçın Arslan & Ilin, 2018) among many others. Still, throughout the teacher education programs, the pre-service teachers' beliefs need to be guided by their actions (Richardson, 2003).…”
Section: Pre-service Teacher Beliefsmentioning
confidence: 99%